Исторические корни волшебной сказки: научное издание / В. Я. Пропп - Пропп Владимир Яковлевич (Лабиринт, 2000)
Экземпляры: Ф. 9 (20201020) / Инвентарный номер: 36334 / Цена: 60.00 / Сис.шифр: 82.3(0) / Авт.знак: П78 / ГРНТИ: 17.71.07 / ББК: 82.3(0)-442